Single and Multi-objective Genetic Programming Methods for Prediction Intervals - Brotto Rebuli, Karina (2023)
Brotto Rebuli, K., Giacobini, M., Tallone, N., & Vanneschi, L. (2023). Single and Multi-objective Genetic Programming Methods for Prediction Intervals. In C. de Stefano, F. Fontanella, & L. Vanneschi (Eds.), Artificial Life and Evolutionary Computation: 16th Italian Workshop, WIVACE 2022, Gaeta, Italy, September 14–16, 2022, Revised Selected Papers (pp. 205-218). (Communications in Computer and Information Science; Vol. 1780). Springer, Cham. https://doi.org/10.1007/978-3-031-31183-3_17